Dexamethasone stimulates store-operated calcium entry and protein degradation in cultured L6 myotubes through a phospholipase A(2)-dependent mechanism - Itagaki, Kiyoshi (American Physiological Society, 2010)
Muscle wasting in various catabolic conditions is at least in part regulated by glucocorticoids. Increased calcium levels have been reported in atrophying muscle. Mechanisms regulating calcium homeostasis in muscle wasting, in particular the role of glucocorticoids, are poorly understood. Here we tested the hypothesis that glucocorticoids increase intracellular calcium concentrations in skeletal muscle and stimulate store-operated calcium entry (SOCE) and that these effects of glucocorticoids may at least in part be responsible for glucocorticoid-induced protein degradation. Treatment of cultured myotubes with dexamethasone, a frequently used in vitro model of muscle wasting, resulted in increased intracellular calcium concentrations determined by fura-2 AM fluorescence measurements. When SOCE was measured by using calcium “add-back” to muscle cells after depletion of intracellular calcium stores, results showed that SOCE was increased 15–25% by dexamethasone and that this response to dexamethasone was inhibited by the store-operated calcium channel blocker BTP2. Dexamethasone treatment stimulated the activity of calcium-independent phospholipase A(2) (iPLA(2)), and dexamethasone-induced increase in SOCE was reduced by the iPLA(2) inhibitor bromoenol lactone (BEL). In additional experiments, treatment of myotubes with the store-operated calcium channel inhibitor gadolinium ion or BEL reduced dexamethasone-induced increase in protein degradation. Taken together, the results suggest that glucocorticoids increase calcium concentrations in myocytes and stimulate iPLA(2)-dependent SOCE and that glucocorticoid-induced muscle protein degradation may at least in part be regulated by increased iPLA(2) activity, SOCE, and cellular calcium levels.